The Concept of an Eco-Efficient Regional Development Strategy: A Case of the Baikal Region - Gunzenova, Karina (European Journal of Sustainable Development, 2020)
The transition to sustainable development requires a comprehensive systematic state policy and suggests a change in existing cultural characteristics that determine the nature of the economic development of society. It assumes reliance on effective mechanisms that can minimize the time and risks of possible destructive processes of such a transition. As a mechanism for institutionalization, we propose using the concept of ecological efficiency as a criterion for the compliance of strategic development plans and relevant regulatory legal acts with the selected course of sustainable development. This work aims to disclose the concept of eco-efficiency through understanding the benefits of focusing on qualitative development criteria. The methodological basis of the study was the provisions of dialectical realism, which determines the variability of the content of quantitative development indices with the constancy of qualitative guidelines, thus ensuring balanced development of civilization for an indefinitely long term. Keywords: sustainable development, ecological efficiency, sustainable development strategy, Baikal region, dialectical realism